2018
DOI: 10.1371/journal.pmed.1002525
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a genetic risk score for atrial fibrillation: A prospective multicenter cohort study

Abstract: BackgroundAtrial fibrillation (AF) is the most commonly encountered arrhythmia and is associated with an elevated risk of stroke. Improving the identification of patients with the highest risk for AF to enable appropriate surveillance and treatment, if necessary, is critical to reducing AF-associated morbidity and mortality. Multiple common single nucleotide polymorphisms (SNPs) are unequivocally associated with the lifetime risk of AF. In the current study we aimed to prospectively validate an AF genetic risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 45 publications
(43 reference statements)
0
23
0
Order By: Relevance
“…The addition of genetic risk factors will allow for even greater refinement. 1,23 It is possible that individuals with asymptomatic AF diagnosed only by ECG represent a different population than those whose AF manifests clinically. Therefore, to optimize future screening programs, the significance of short episodes of AF, especially when asymptomatic, will require greater clarity.…”
Section: Research Original Investigationmentioning
confidence: 99%
“…The addition of genetic risk factors will allow for even greater refinement. 1,23 It is possible that individuals with asymptomatic AF diagnosed only by ECG represent a different population than those whose AF manifests clinically. Therefore, to optimize future screening programs, the significance of short episodes of AF, especially when asymptomatic, will require greater clarity.…”
Section: Research Original Investigationmentioning
confidence: 99%
“…Predisposition to AF appears to also be influenced by polygenic risk factors, though their clinical utility is not clear at this time (Muse et al, 2018; Nielsen et al, 2018; Weng et al, 2018). Trends from long-term longitudinal cohort studies in the United States have also found increasing prevalence of AF though AF incidence has been stable (Schnabel et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…GRS was used to identify patients with Mendelian and complex disease 25 patterns known as loci for HF risk factors, such as CAD, Cardiometabolic Disease, 8,26 Blood Pressure 9 and atrial fibrillation. 27 Heart failure has similar or worse prognosis when compared to most cancers. 28 Traditional risk factors 20 have been used in risk prediction.…”
Section: Discussionmentioning
confidence: 99%